A Scoping Review of Pain Management Education Programs (PMEPs): Do They Prepare Nurses to Deal with Patients’ Postoperative Pain? - Manaporn Chatchumni; Henrik Eriksson; Monir Mazaheri (Pain Research and Management)
This is a report of a scoping review undertaken to obtain an overview of studies conducted on pain management education programs (PMEPs). The aim of this review was to describe existing research publications relating to PMEP to map how pain management practice training might directly influence surgical nurses in contributing to successful pain outcomes in patients. The initial search of electronic databases identified 40 articles according to the inclusion criteria and search strategy, which applied the following terms: (“Pain management education program”) AND∗ OR∗ (“Nurses”) AND∗ OR∗ (“Patient outcomes”) AND∗ (“Mixed methods”). Titles, abstracts, and keywords were also searched for the term “Nurse education.” After applying exclusion criteria, five relevant peer-reviewed articles were eventually selected for the final charting of the data. The search included articles published between January 2015 and March 2019. The results show that PMEPs employ a variety of computer-based simulation, web-based facilitation, and video materials based on an evidence-based approach in their syllabuses. PMEPs were shown to enhance practice by promoting improved skills in critical thinking, leadership, patient management, and health promotion. Additionally, these programs promote an ability to practice across a variety of inpatient and outpatient settings, wherein nurses’ engagement in managing patients’ pain increased after completing the PMEP. Research within PMEP indicates that these programs may contribute to promoting opportunities for new collaborations within multidisciplinary team projects. Additionally, further research initiatives are needed to explore various aspects of these programs to enhance the nursing skills required for effective pain management, such as computer-based simulation, web-based facilitation, and video materials. Moreover, research relating to PMEPs in low- and middle-income countries is scarce and warrants further study.